TIPOLOGI GATE DI DAERAH ISTIMEWA YOGYAKARTA - , IRWAN IRIYANTO, Ir. Ikaputra, M.Eng., Ph.D. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The emergence of various phenomena gate in Yogyakarta with a variety of territory and authority in it allegedly has links with identity and the identity of Yogyakarta. This study aims to understand the phenomenon of the gate through typology studies which include: (a) typology based gate function